Integration of Local Wisdom in Social Studies Learning to Realize The Pancasila Student Profile in Elementary Schools - Izzah, Navisatul; Widyawati, Merinda Wike; Devita, Silvana Mei; Fiqrizzakiyah, Nadia (Program Studi PGMI, Universitas Al Falah As Sunniyah Kencong Jember, 2025)
This research aims to identify forms of local wisdom relevant for integration in Social Studies learning in elementary schools and demonstrate their relationship with the Pancasila Student Profile dimensions, analyze effective strategies and learning models in integrating local wisdom, and evaluate the influence of Social Studies learning integrated with local wisdom on the formation of Pancasila values and elementary school student character. This research uses a qualitative approach with an interpretive paradigm and multi-site case study design involving three elementary schools in urban, suburban, and rural areas. Research subjects include Social Studies teachers, students in grades IV-VI, parents, and community leaders. Data collection techniques were conducted through participatory observation, in-depth interviews, focus group discussions, documentation studies, and open questionnaires. Data were analyzed using thematic analysis techniques with data triangulation to increase research validity. Research results show that the forms of local wisdom integrated include traditional organic farming practices, mutual cooperation systems, customs, traditional medicine knowledge, folk stories, and local handicraft traditions, all of which have meaningful relationships with the Pancasila Student Profile dimensions. Effective learning strategies include contextual learning (CTL), project-based learning, collaboration with community leaders, narrative learning based on folk stories, and outdoor learning with structured field trips. The combination of strategies with local context adjustments proved most effective. Social Studies learning integrated with local wisdom significantly influences the formation of Pancasila values and student character, demonstrated by a 45 percent increase in understanding Pancasila values, strengthening of cultural and national identity (92 percent of students), development of mutual cooperation and empathy character (78 percent of students), 3.5-fold increase in social participation, and learning motivation increasing from 65 percent to 87 percent. This research proves that the integration of local wisdom in Social Studies learning is an effective and meaningful strategy to realize the Pancasila Student Profile, not only increasing conceptual understanding but also building strong connections between students and their communities, strengthening cultural identity, and encouraging students to become agents of positive change in society